A Multi‐Level Approach to Direct and Indirect Relationships between Organizational Voice Climate, Team Manager Openness, Implicit Voice Theories, and Silence. Issue 2 (16th February 2020) - Knoll, Michael; Neves, Pedro; Schyns, Birgit; Meyer, Bertolt
Abstract : Employee silence impedes sustainable organizational development, and it can conceal harm for internal and external stakeholders. Established approaches to overcoming silence in organizations draw on the assumption that employees withhold their views based on deliberate elaborations on the effectiveness and risks they associate with voice. Our research aims at complementing these approaches. Applying an information processing approach to culture and using implicit voice theories (IVTs; i.e., taken‐for‐granted beliefs about when and why speaking up at work is risky or inappropriate) as an example, we introduce a model proposing ways through which shared implicit knowledge structures emerge in teams and organizations, and how they affect motives to remain silent. We examine parts of the model with a sample of 696 employees nested in 129 teams and 67 organizations. Our findings show that IVTs can be shared at the team and organizational level, that shared IVTs explain variance in silence motives above and beyond perceptions of organizational climate and manager openness at the team and organization level, and that IVTs function as a mediator between team manager openness and silence motives. In sum, our findings point at shared IVTs as a way to conceptualize underlying basic assumptions of cultures of silence.